UPAYA PENINGKATAN KETRAMPILAN BAGI PENYANDANG TUNA RUNGU- TUNA WICARA (STUDI KASUS DI SLB B-C SURYAWIYATA JAKARTA) - Lidang, Sari; Dwiyantari, MM Sri (Jurnal Insani, 2020)
This study aims to provide an overview of (1) the problems experienced by people with speech-impaired disabilities in participating in skills training, (2) what roles are performed by social workers in trying to solve these problems and (3) how the outputs of social workers' efforts through their roles are: the role he performs. This research is an action research, with case study method. The case analyzed was a group of 12 students from SLB Suryawiyata who were accompanied by social workers in the process of their skills training. The results of the study indicate that: (1) The problems that occur in deaf and speech-impaired students are that students' skills are less than optimal, (2) the role of social workers in assisting students so that the results of optimal skills training are as brokers, educators and facilitators and (3) outputs of assistance by social work is an increase in students' skills in operating computers, skills in dancing and skills in making handicrafts. It is hoped that with optimal assistance efforts, the disabled people with hearing impairment will be transformed into able ones.